2009
DOI: 10.1007/s11127-009-9483-2
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model of the 2007 Russian Duma election

Abstract: Stochastic model, Election, Russian Duma, H10,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…For both countries, our estimations suggest that the low valences of the opposition parties has meant that they have been unable to mount a serious challenge to the government regime. This parallels a result found by Schofield and Zakharov (2010) for the Russia Dumma election of 2007, which showed that there was a similar valence weakness of the parties opposed to United Russia, the party supportive of then President Putin.…”
Section: Introductionsupporting
confidence: 84%
“…For both countries, our estimations suggest that the low valences of the opposition parties has meant that they have been unable to mount a serious challenge to the government regime. This parallels a result found by Schofield and Zakharov (2010) for the Russia Dumma election of 2007, which showed that there was a similar valence weakness of the parties opposed to United Russia, the party supportive of then President Putin.…”
Section: Introductionsupporting
confidence: 84%
“…Even though the necessary condition for convergence is not met, the analysis done in Schofield and Zakharov (2010) shows that Fair Russia, with the lowest valence, maximizes its vote share by remaining close to the electoral mean. This result, however, highlights that unexpected political events could prompt Fair Russia to move from the origin.…”
Section: The 2007 Russian Electionmentioning
confidence: 99%
“…The analysis carried out in Schofield and Zakharov (2010) concentrates on four parties: the pro-Kremlin United Russia party (ER), the Liberal Democratic Party (LDPR), the Communist Party (CPRF) and the Fair Russia (SR). Voters' ideological preferences were measured using the survey conducted by the Russian Public Opinion Research Center in May 2007.…”
Section: The 2007 Russian Electionmentioning
confidence: 99%
“…Based on this, 34 The exact wording of the question and descriptions are available in the Appendix. 35 Factor-analytic techniques to estimate policy platforms from these concrete issue item batteries have been used in various articles concerned with spatial voting decisions (see Schofield et al 1998;Schofield and Zakharov 2009;Stoetzer and Zittlau 2015;Quinn, Martin, and Whitford 1999). 36 A more detailed description of the results is provided in the Appendix.…”
Section: Measurement Of Inconsistency and Policy Platforms In The Amementioning
confidence: 99%